2019
DOI: 10.1017/jog.2019.83
|View full text |Cite
|
Sign up to set email alerts
|

Formation and evolution of an extensive blue ice moraine in central Transantarctic Mountains, Antarctica

Abstract: Mount Achernar moraine is a terrestrial sediment archive that preserves a record of ice-sheet dynamics and climate over multiple glacial cycles. Similar records exist in other blue ice moraines elsewhere on the continent, but an understanding of how these moraines form is limited. We propose a model to explain the formation of extensive, coherent blue ice moraine sequences based on the integration of ground-penetrating radar (GPR) data with ice velocity and surface exposure ages. GPR transects (100 and 25 MHz)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 58 publications
1
44
0
Order By: Relevance
“…The blue ice moraine at the base of Mount Achernar has a core of glacier ice hundreds of meters thick, which is fed by upward-flowing ice from the Law Glacier (Kassab and others, 2016). Here, sediment emerges through the sublimation of the underlying ice (Bader and others, 2017).…”
Section: Field Site and Methodsmentioning
confidence: 99%
“…The blue ice moraine at the base of Mount Achernar has a core of glacier ice hundreds of meters thick, which is fed by upward-flowing ice from the Law Glacier (Kassab and others, 2016). Here, sediment emerges through the sublimation of the underlying ice (Bader and others, 2017).…”
Section: Field Site and Methodsmentioning
confidence: 99%
“…Achernar Moraine, Central -Transantarctic Mountains. Approximate flowlines on Law Glacier are illustrated both down glacier and into the moraine (Kassab et al, 2020). Digital Globe imagery (©2014) provided by the Polar Geospatial Center (St. Paul, Minnesota, USA) Figure 2: Abundance of selected elements, minerals, and amorphous phases in rock compared with the fine fraction of emerging subglacial sediments.…”
Section: Figure Captionsmentioning
confidence: 99%
“…Studies here have characterized till composition and provenance (Bader et al, 2017), soil formation (Scarrow et al, 2014), and the timing of till accumulation (Graly et al, 2018b;Kaplan et al, 2017). Ground penetrating radar measurements at the site have shown that the sediment in the moraine sources from the glacier bed and accumulates laterally over time (Kassab et al, 2020). Stable isotopes of O and H in the moraine's ice suggest that sediment entrainment occurred in the presence of liquid subglacial water, upstream from the moraine, at the margin of the polar plateau (Graly et al, 2018c).…”
Section: Introductionmentioning
confidence: 98%
“…The basal thermal regime also affects the likelihood of erosion and transport by the overlying ice, with the maximum degree of scouring and entrainment occurring in areas at the transition between basal melting upstream and basal freezing downstream 54 . Finally, both MA113 and PRR50489 are found in areas with very slow modern ice velocities 25,55 , which likely limits their transport distance to <50 km 31 . We therefore propose that the cycles of basal melting and freezing indicated by opal-calcite precipitates are the result of migrations of the basal thermal and hydrologic boundary, causing changes in the connectivity between waters from the interior and edge of the ice sheet following millennial-scale climate cycles (Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2). These samples were precipitated over tens of thousands of years in subglacial aqueous systems on the EAIS side of the Transantarctic Mountains (TAM), and were subsequently eroded and transported in exhumed sections of basal ice to be finally deposited on the surface within supraglacial moraines 25 . PRR50489 and MA113 are 3 and 9cm thick respectively, with alternating layers of calcite and opal (Extended Data Fig.…”
Section: Changes In Subglacial Precipitate Mineralogy Correlated With...mentioning
confidence: 99%